Gender differences in the experience of loneliness among adolescents in Jakarta - Komang Bara Wedaloka; Sherly Saragih Turnip (HUMANITAS: Indonesian Psychological Journal, 2019)
Adolescence is a transition period from childhood to adulthood. During this period, adolescents are prone to problems, one of those problems being loneliness. This research aimed to find out gender differences in the experience of loneliness among adolescents in Jakarta. Six hundred sixty-two participants, which consisted of 318 male and 344 female students aged between 15-20 years old, were selected from five schools by using multi-stage random sampling. 6-Item (short) De Jong Gierveld Loneliness Scales were used to measure loneliness. Data was collected through school-based research conducted on senior high school students in the Special Capital Region of Jakarta. The results show that there are significant differences in loneliness between male and female adolescents in overall, emotional and social dimensions. Female adolescents had significantly higher scores of loneliness compared to male adolescents, not only overall but also in emotional and social dimensions.